2019
DOI: 10.1021/acsami.9b06889
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte-Dependent Oxygen Evolution Reactions in Alkaline Media: Electrical Double Layer and Interfacial Interactions

Abstract: Traditional understanding of electrocatalytic reactions generally focuses on either covalent interactions between adsorbates and the reaction interface (i.e., electrical double layer, EDL) or electrostatic interactions between electrolyte ions. Here, our work provides valuable insights into interfacial structure and ionic interactions during alkaline oxygen evolution reaction (OER). The importance of inner-sphere OH − adsorption is demonstrated as the IrO x activity in 4.0 M KOH is 6.5 times higher than that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 58 publications
1
58
0
Order By: Relevance
“…For the OER, previous studies have shown that the presence of different cations in the electrolyte can have an important effect in the catalytic performance of different transition oxide materials including IrO x. …”
Section: Figurementioning
confidence: 64%
“…For the OER, previous studies have shown that the presence of different cations in the electrolyte can have an important effect in the catalytic performance of different transition oxide materials including IrO x. …”
Section: Figurementioning
confidence: 64%
“…Upon the application of higher voltage, the electrons try to flow through the external circuit and the OHions attempt to cross the AEM. However, due to internal barriers, the electrons and OHions are not able to transfer at lower voltages 24 . Hence, there is a decrease in hydrogen production due to the voltage drop-this is referred to as the activation overpotential or charge transfer resistance (R CT ).…”
mentioning
confidence: 99%
“…In the assignment of the charge transfer resistances this indicates a decreased activity of OER with increasing KOH concentration. However, it is to be supposed that both HER and OER kinetic improve with increasing the KOH concertation, which should result in a reduction in activation loss . This surprising observation for the OER can be explained when considering that increasing concentration of KOH also leads to an increased viscosity, which influences hydrodynamic transport properties, like diffusion, convection, but also bubble formation and bubble detachment .…”
Section: Resultsmentioning
confidence: 99%